2007
DOI: 10.1111/j.1475-6765.2007.00700.x
|View full text |Cite
|
Sign up to set email alerts
|

Major findings and paths for research: A concluding note

Abstract: Abstract.  In this concluding note, the editors of this special issue first produce a synthesis of the findings of the empirical cases. Regarding delegation problems in the participatory devices under scrutiny, the conclusions are contrasting, and the outcome depends very much on the institutional design of each procedure, and on the kind of skills that are necessary to participate. Regarding the quality of deliberations, moderately positive conclusions are reached as a rule. With respect to the efficiency of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 13 publications
(13 reference statements)
0
8
0
Order By: Relevance
“…Visibility and publicity of participatory processes should be part of their evaluation, as others have already suggested (Papadopoulos & Warin 2007b). By analysing interaction models, it was shown that awareness of local politics moderates the effect of PIs on procedural fairness.…”
Section: Discussionmentioning
confidence: 87%
See 3 more Smart Citations
“…Visibility and publicity of participatory processes should be part of their evaluation, as others have already suggested (Papadopoulos & Warin 2007b). By analysing interaction models, it was shown that awareness of local politics moderates the effect of PIs on procedural fairness.…”
Section: Discussionmentioning
confidence: 87%
“…Dryzek 2002;Gutmann & Thompson 2002). Critical voices have, however, questioned their visibility and publicity in the eyes of lay citizens (Papadopoulos & Warin 2007b), which is an important precondition for the broader contributions of PIs to the democratic system. New forms of public engagement are saluted also in the field of public administration and governance, where they are seen as important sources for local knowledge (Fischer 2000) and potential responses to wicked problems (Raisio 2010).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Alternatively, the structural barriers to participation in democratic states may have been underestimated. According to the path dependence hypothesis, democracies may be using such processes as a façade while capturing more control over management [58].…”
Section: Discussionmentioning
confidence: 99%